2018
DOI: 10.1371/journal.pone.0190145
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of a community-based intervention to improve maternal and neonatal health service coverage in the most rural and remote districts of Zambia

Abstract: BackgroundA community-based intervention comprising both men and women, known as Safe Motherhood Action Groups (SMAGs), was implemented in four of Zambia’s poorest and most remote districts to improve coverage of selected maternal and neonatal health interventions. This paper reports on outcomes in the coverage of maternal and neonatal care interventions, including antenatal care (ANC), skilled birth attendance (SBA) and postnatal care (PNC) in the study areas.MethodologyThree serial cross-sectional surveys we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…This nding is supported by other evidence which shows a positive relation between IPPFP use and FP counseling before or during delivery [28]. Studies have shown MWHs remain an important window of opportunity to provide access to FP messages and to offer women with various options of contraceptive methods [29,30]. Therefore, the study nding informs the need for service integration within the different service units in the public health facilities to take advantage of the MWHs to increase IPPFP uptake.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This nding is supported by other evidence which shows a positive relation between IPPFP use and FP counseling before or during delivery [28]. Studies have shown MWHs remain an important window of opportunity to provide access to FP messages and to offer women with various options of contraceptive methods [29,30]. Therefore, the study nding informs the need for service integration within the different service units in the public health facilities to take advantage of the MWHs to increase IPPFP uptake.…”
Section: Discussionsupporting
confidence: 67%
“…Note applicable. MWH refers to a waiting area/house prepared in a health center compound for pregnant women identi ed to be at risk who receives services, including health services, and later to delivers with a skilled provider in a facility [30]. Women who stayed in MWH =1, 0=otherwise…”
Section: Consent For Publicationmentioning
confidence: 99%
“…Each of the seven districts are also target sites for the Saving Mothers, Giving Life (SMGL) initiative, a public– private partnership aimed at accelerating reductions in maternal mortality by improving health systems and addressing the delays in seeking, reaching, and receiving care in Nigeria, Uganda, and Zambia. 25 In addition to general health system-strengthening approaches, key activities of SMGL include: 1) community mobilization activities to increase demand through community leaders and volunteers trained in delivering messages and supporting pregnant women, known as Safe Motherhood Action Groups (SMAGs); 26 2) infrastructure development and improvements to transport and communication systems to increase access to and availability of services; and 3) strengthening health facility capacity to manage obstetric complications and improve quality of care. 25 The first proof-of-concept phase of SMGL was launched in 2012 and targeted Chembe, Kalomo, Lundazi, Mansa, and Nyimba districts.…”
Section: Methodsmentioning
confidence: 99%
“…All analyses were conducted using Stata version 13 [19]. Data were cleaned and adjusted for multistage cluster sampling using the 'svyset' survey command [20,21] During the analysis, the weights were taken into account at each stage of the analysis, ensuring nationally representative estimates. Proportions were used to describe the data.…”
Section: Discussionmentioning
confidence: 99%